OPTIMAL FLOCK STRUCTURE OF PIG FARM PROVIDING MINIMUM COSTS - Mičić, Ivan; Rajić, Zoran; Živković, Jelena; Orović, Dragan; Mičić, Marko; Mičić, Ivana; Mičić, Marija (Economics of Agriculture, 2017)
The study deals with the analysis of production costs, as well as the net area in the production of the herd of organizational structures at the pig farm. The question arises of the optimum production structure in the cooperative household, which is mainly oriented to the production of Pigmeat. In this paper, a concrete model of linear programming for the optimal organizational structure of the herd of pig farms of the net effective area was defned. The research covered the cooperative farm "1.Decembr" in Žitorađa in Toplički district. For 2013, the production technology of agricultural animals was followed, and economic results were analyzed. In the observed period of one year. It was found that there were 28,252 throats on the farm. Total agricultural growth in 2013 amounted to 664,920 kg, in the amount of 781,569.7 €. Total death: piglets on wolves 6,315 throats, stuffed pigs 3,425 throats, 17,150 kg, tooth 928 throats, 40,980 kg, pigs 67 throats 13,930 kg, immature 3 throat 890 kg